Protrieve sheath utilization for capturing supra-filter thrombus during a retrieval of thrombosed and embedded IVC filter - Annabella Shewarega; Taylor M. Powell; Douglas Silin (CVIR Endovascular, 2023)
Abstract Background Inferior vena cava (IVC) filters, while effective in preventing pulmonary embolism, can increase the risk of IVC thrombosis. IVC filter (IVCF) thrombosis can result from emboli getting trapped within the filter, extension of deep vein thrombosis (DVT), or the device’s inherent thrombogenicity causing in situ thrombosis. This condition can cause noticeable clinical symptoms and complicate the removal of the filter due to the potential for thromboembolism, often resulting in temporary filters remaining unextracted. This case report highlights a novel approach employed to mitigate the risk of thromboembolism during the procedure by capturing mobilized thrombus proximally to the entrapped IVCF. Case presentation A 54-year-old woman with a complex medical history including cerebral palsy, Crohn’s disease, and transfusion-dependent iron-deficiency anemia experienced a pulmonary embolism. Due to failed anticoagulation therapy resulting in gastrointestinal bleeding and high transfusion requirements, she underwent placement of an IVCF as a preventive measure against recurrent pulmonary embolism. Three years later, the patient presented with lower extremity swelling and a sudden decline in hemoglobin levels. Diagnostic imaging revealed adherent nonocclusive thrombus within and above the indwelling IVCF. Utilizing the novel Protrieve sheath with the self-expandable Nitinol funnel, successful endovascular removal of the embedded IVCF and adherent thrombus was performed, while mitigating the risk of intraprocedural pulmonary embolism. Conclusions The successful intraprocedural trapping and removal of mobilized thrombus from the IVCF removal was achieved using the Protrieve sheath and Nitinol funnel. This approach provides a promising solution to reduce the risk of embolization during the removal of thrombosed IVCFs, potentially outweighing the complications associated with filter removal.